Options by context approach to agronomic innovation profoundly changed International, Government, NGO and private sector policy and practice across 14 countries. - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
FTA produced a paradigm shift in agronomy supporting local innovation across three continents. Diverse and inclusive agroecological options that result, impact food security, farm income and environmental resilience for over 3.769 M people on 2.496 M ha and are part of global initiatives targeting 100 M smallholder farmers.